Neuroeconomics - Reuter, Martin; Montag, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg (Imprint), 2016)
This book represents one of the cornerstones of the series Studies in Neuroscience, Psychology and Behavioral Economics. It is divided into eight sections, starting with an introduction to neuroeconomics followed by an overview of frequently applied experimental paradigms (games) in neuroeconomics research. Furthermore, it addresses the molecular basis of human decision making, environmental/situational factors and social contexts influencing human decision making, as well as translational and developmental/clinical approaches to neuroeconomics. In closing, a paper on neuro-marketing demonstrates how knowledge from neuroeconomics research can be applied in "real life." Culminating in an extensive methods section, in which eight different neuroscience techniques are introduced, the book offers an essential resource for researchers and practitioners, and may also be beneficial for graduate students.
Introduction into the Field of Neuroeconomics -- Historical Aspects of Neuroeconomics -- Game Theory and Human Decision Making -- Paradigms in Neuroeconomics -- Human Decision Making and the Brain: Structure and Functionality of the Central Nervous System -- Methods in Neuroeconomics -- Hormones -- Genetics -- Empirical Findings in Neuroeconomics - State of the Art -- Loss Aversion -- Trust -- Risk -- Impulsivity -- Dictator game -- Ultimatum Game -- Third Party Punishment -- Decision Making under Ambiguity -- Altruism -- Pathological Decision Making.
Keywords: Consciousness; Neurosciences